On the performance of ground coupled seasonal thermal energy storage for heating and cooling: A Canadian context - Fong, M. (Elsevier Ltd, 2019)
This study examines the feasibility of capturing and storing the coolth from the winter and the heat from the summer in the ground by utilizing the groundwater's ability to phase change as a storage media. A novel system that implements a bayonet tube heat exchanger is proposed in this study due to it's simple design and ease of installation using a single drill hole. A lab-scale experiment of a thermally controlled ground simulator was conducted to provide a proof-of-concept of the energy storage mechanism. A conjugate, multiphase heat transfer model was developed taking into account conversation of mass, momentum and energy and validated using the experimental results. The model framework is then extended to study the energy storage potential at full scale for four Canadian cities. The first set uses an averaged sinusoidal temperature profile, while the other set uses hourly temperatures from weather monitoring stations. Results of the study showed the long-term aggregated energy extraction was similar between both sets, however, over the short-term the results are more chaotic due to the nature of the weather. The system is thus best suited as a pre-heating or pre-cooling stage, making use of low-grade heat/cooling to decrease the need to use high grade energy (electricity or natural gas) over which the operator has stronger control. Â© 2019